The Temporality of Contemporaneity and Contemporary Art: Kant, Kentridge and Cave Art as Elective Contemporaries. Issue 4 (December 2021) - Hughes, Fiona
Abstract: This article contributes to understanding of Contemporary Art and of the temporality of contemporaneity, along with the philosophy of time more generally. I propose a diachronic contemporaneity over time gaps – elective contemporaneity – through examination of Kant's Transcendental Aesthetic, the Third Analogy and the concept of 'following' among artistic geniuses; diachronic recognition and disjunctive synchronicity discoverable in William Kentridge's multimedia artworks; as well as non-chronological temporal implications of superimpositions in late Palaeolithic cave art suggesting 'graphic respect'. Elective contemporaneity shows up complexity in relations to past and present, putting in question definitions of 'Contemporary Art' restricted to either chronology or supposedly definitive paradigms.